Cuidado da enfermeira à gestante na perspectiva cultural - Alves, Camila Neumaier (2014)
Pregnancy is a physiological event that can generate changes in physical, emotional, economic and social life of the woman. The nursing care performed prenatally should involve the context in which the pregnant woman is inserted, including her family, along with recognition of the care practices, beliefs and values. On this track of thought, this dissertation has as its object of the study nursing care to pregnant women from a cultural perspective, and as a guiding research question "how nurses of the primary health care, in the city of Santa Maria, experience the practice of care with pregnant woman, from a cultural perspective?". The aim of this study is understand, from the cultural perspective, the care practices and the cultural values of nurses while caring for pregnant women. The theoretical and methodological framework was based on the Theory of Diversity and Universality Cultural Care, proposed by Madeleine Leininger. It was a field research, qualitative, with ethnographic perspective. The research scenario was four basic care of the city of Santa Maria. The informants were five nurses working in prenatal care activities. The method used was based on ethnonursing enablers guides Observation - Participation Reflection and semistructured interview. Data analysis followed the guide analysis proposed by Leininger. The research was compliance with the provisions of Resolution No. 196/96 of the National Council of Health. This research allowed to comprehend how the nurse care is developed in low risk prenatal care and also the culture influence in this process. It is conceived that constructed values in familiar formation, religion and educational background, political views and individualities of each one of the nurses are interconnected and present in their care actions. Therefore, understand the other's way of life, their beliefs and care practices provides cultural bases to realize the care in an integrally form, buoyed in reflection and autonomy in the decision making.